Bibliometric Analysis of Exercise Therapy: Trends, International Collaboration, and Innovation in Athlete Rehabilitation - Hasanuddin, M. Iqbal; Akhmad, Noor; Mughataz , Mustafa Hussein (LITPAM, 2026)
This study explores the development of exercise therapy research for athlete rehabilitation, with a total of 966 Scopus-indexed articles published between 1973 and 2025, demonstrating a significant increase since 2011 and peaking in 2023. A quantitative bibliometric approach was employed to map publication trends, author and institutional distributions, international collaboration patterns, journal distributions according to Bradford’s Law, subject areas, as well as conceptual structures and keyword clusters, using VOSviewer and Bibliometrix for analysis. The findings indicate that publications are concentrated among a small number of authors, institutions, and core journals, with primary research orientations including injury rehabilitation, performance enhancement, physiological regulation, and cardiovascular safety. Keyword cluster analysis identified six thematic orientations emphasizing musculoskeletal injury management, physiological recovery, tendon and knee rehabilitation, performance and conditioning, cardiovascular risk, and professional and clinical practice. These findings confirm that exercise therapy research has evolved into a complex and integrated multidisciplinary field, offering theoretical and practical contributions to the development of more holistic and safe evidence-based rehabilitation interventions. The study also highlights the need for longitudinal and interdisciplinary research, particularly for non-elite populations and specific cardiovascular risks, to strengthen the scientific foundation and practical application of athlete rehabilitation.